A preliminary study of educational leadership in the rural context in Malaysia / Mary Yap Kain Ching and Siow Heng Loke - Yap Kain Ching, Mary Kain Ching; Siow, Heng Loke (Universiti Teknologi MARA, 2016)
The paper focused on the review of literature particularly in relation to rural education in the Malaysian context. This exposed the scarcity of research on effective leadership practices in rural context especially in Malaysia. This awareness is an impetus for future researchers to venture into this issue and subsequently contribute to the knowledge corpus of effective leadership practices in the rural context. The paper also put forth a review of a preliminary study conducted on an award winning Head Teacher as observed in a rural primary school in Sarawak who had elevated his school to a higher stratum by clinching an international award, the Commonwealth Education Good Practice Award. Unstructured observations and informal interviews had been conducted and the data collected had been analysed using open, axial and selective coding processes. The preliminary findings had been mapped onto five main settings namely human, interactional, physical, programme and emotional. The review of this preliminary study exemplified the value of investigating leadership practices particularly in their specific rural context as different contexts might entail different leadership practices.